AI as Systems Engineering Augmented Intelligence for Systems Engineers. Issue 1 (15th April 2020) - Rouse, William B.
ABSTRACT: AI technology's rapid development has led to various arguments for SE for AI, as well as AI for systems engineering. This article argues for and illustrates a third perspective — AI as systems engineering. A conceptual architecture articulates employing AI as an assistant systems engineering engineer. This cognitive assistant understands systems engineering concepts, principles, methods, and tools as well as the workflows and preferences of the particular supported engineer. The vision is a cognitive assistant understanding your domain, your current intentions, and you.